Apoptosis is not conserved in plants as revealed by critical examination of a model for plant apoptosis-like cell death - Minina, Alyona; Dauphinee, Adrian N; Ballhaus, Florentine; Gogvadze, Vladimir; Smertenko, Andrei P.; Bozhkov, Peter V. (BMC biology, 2021)
Animals and plants diverged over one billion years ago and evolved unique mechanisms for many cellular processes, including cell death. One of the most well-studied cell death programmes in animals, apoptosis, involves gradual cell dismantling and engulfment of cellular fragments, apoptotic bodies, through phagocytosis. However, rigid cell walls prevent plant cell fragmentation and thus apoptosis is not applicable for executing cell death in plants. Furthermore, plants are devoid of the key components of apoptotic machinery, including phagocytosis as well as caspases and Bcl-2 family proteins. Nevertheless, the concept of plant “apoptosis-like programmed cell death” (AL-PCD) is widespread. This is largely due to superficial morphological resemblances between plant cell death and apoptosis, and in particular between protoplast shrinkage in plant cells killed by various stimuli and animal cell volume decrease preceding fragmentation into apoptotic bodies.